2013
DOI: 10.1016/j.ypmed.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs, behaviors and HPV vaccine: Correcting the myths and the misinformation

Abstract: Most fears related to HPV vaccine are more related to myth than reality. In the absence of major health policy initiatives, such as those implemented in Canada, the U.K., and Australia, a multi-level, multi-faceted approach will be required to achieve high rates of HPV vaccination. It will be essential to focus on the education of HCPs regarding indications for HPV vaccination and approaches to communicating most effectively with parents and patients about the safety and benefits of vaccination and the risks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
128
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 68 publications
10
128
0
2
Order By: Relevance
“…The rate of those who received professional training about cervical cancer and HPV infection was low among the students who studied at both health department and non-health department and the rate of those who wished to have more information was higher among the students who studied at health departments; which emphasized the educational gap among the female students (Table 4). In many countries; it was reported that the rate of having HPV vaccination was below the optimal levels (Zimet et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of those who received professional training about cervical cancer and HPV infection was low among the students who studied at both health department and non-health department and the rate of those who wished to have more information was higher among the students who studied at health departments; which emphasized the educational gap among the female students (Table 4). In many countries; it was reported that the rate of having HPV vaccination was below the optimal levels (Zimet et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For parents of adolescent boys the 1-sided message was slightly altered, and excluded the reference to cervical cancer prevention. Parents of adolescents in the two-sided message condition received this additional statement, which has been identified as a common concern about HPV vaccination 21 : "Some parents want to wait until more adolescent boys/girls have been given this vaccine before getting their own son/daughter vaccinated. However, this vaccine has been licensed for 5 y and over 72 million doses worldwide have been given to adolescent girls and boys as well as young adult women and men.…”
Section: Interventionmentioning
confidence: 99%
“…The literature on parental HPV vaccine decision-making cites several barriers to vaccination including: a lack of research on the long term efficacy and side effects of the vaccine, the age of vaccination administration being too young, mistrust of pharmaceutical companies, and fears that the vaccine would promote early sexual activity and/or reduce self-protective sexual behaviors -also referred to as sexual disinhibition or risk compensation. [16][17][18] In addition, the cost of the HPV vaccine (which is approximately $450 CAD for 3 doses) has been reported as one of the principal barriers to vaccination. 19,20 Implementation of publicly funded HPV vaccination programs across Canada removes the barrier of cost, thus allowing unhindered exploration of other factors that impact parental attitudes and beliefs concerning vaccination.…”
Section: Introductionmentioning
confidence: 99%